Les pesticides, un risque pour la santé ? - Nolwenn Bühler; Sarah Waeber (Revue d'anthropologie des connaissances)
This article looks at the way in which uncertainties and confusion associated with the health risks posed by pesticides are constructed on a daily basis among the farming professionals of the canton of Vaud (Switzerland). Drawing on the “production of ignorance” (Counil & Henry, 2016; Dedieu, 2022) conceptual framework, the article examines the role of farmers in maintaining confusion about the toxicity of these products. Focusing on experiential knowledge (Rabeharisoa et al., 2014), the article presents two dynamics of ignorance production. On the one hand, we examine the central role of bodily and sensitive experiences in the creation of an “ignorance loop” (Durant, 2020), i.e. an iterative cycle of co-constitution of ignorance. We also ask how everyday pesticide management practices influence the dynamics of trust and mistrust at work in farmers' relationships with the authorities that approve and regulate pesticides, and towards science. This analysis highlights the importance of farmers' dependence on the agri-food industry and policy, as well as the deleterious effects of the stigma faced by this profession, as two major factors maintaining confusion and ignorance about the dangerousness of pesticides.